KOMUNIKASI TRANSENDENTAL DALAM PELAKSANAAN UPACARA TUMPEK PENGATAG DI DESA BANYUATIS KABUPATEN BULELENG - Ketut Yuniati (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2022)
The Tumpek Pengatag ceremony is a form of relationship between humans and plants which has the essence of expressing gratitude to Sang Hyang Sankara as a manifestation of God in creating all types of plants (sarwatumuwuh) for human life and prosperity. The form of the Tumpek Pengatag ceremony is a special form of sacred ceremony as a form of expression of their souls in establishing a vertical communication relationship with the supernatural world and the surrounding environment. In this context it can be said that in the series of Tumpek Pengatag Ceremony there are communication practices in it, one of which is transcendental communication. This study tries to carry out transcendental communication which is carried out by the process of implementing the Tumpek Pengatag Ceremony in Banyuatais Village, Buleleng Regency. The formulation of the problem in this research is how the process, form and meaning of transcendental communication in the implementation of the Tumpek Pengatag ceremony. This research is a qualitative research with data collection obtained through interviews involving 10 people, direct observation and documentation. While the theoretical basis used is the theory of taste, the theory of semiotics and the theory of communication sadharanikaran. The results of this study indicate that the process of transcendental communication in the Tumpek Pengatag ceremony occurs vertically, namely human communication as a communicator and God as a communicant. While the form of this transcendental communication is verbal and non-verbal communication. The meaning of transcendental communication in the Tumpek Pengatag ceremony is the meaning of gratitude and the meaning of satisfaction.Keywords: Transcendental Communication, Tumpek Pengatag Ceremony